Latihan Kepemimpinan, Managemen dan Organisasi Bagi Siswa SMA Negeri Selangit Kabupaten Musi Rawas - Yadri Irwansyah; Maria Ramasari; Sarkowi Sarkowi (Lembaga Pengembangan Kinerja Dosen, 2024)
This basic leadership, management and organization training stems from the very minimal knowledge and experience of students in these materials, students who participate and are active in organizations at Selangit State High School only view organizations as merely additional or extracurricular activities, without understanding the substance in them. management of the organization. The aim of this training is to provide students with direct insight and experience regarding leadership and organizational management theories. The method in this training is an interactive lecture and discussion method, where students are invited to actively participate in these activities. As a result of this training, students gain additional knowledge and experience regarding organizational management.